Assessment of certificate program pedagogical formation education students in terms of their technopedagogic field information competencies and attitudes towards teaching profession - Tuncer, Murat; Dikmen, Melih (My University, 2016)
Technology and technological developments increasingly appear in human life day by day. As a result of that, learners and employees feel the need of constantly renewing and developing themselves. The development of technology has brought along change as well in the education sector as well as many other industries. Developments in the field of education have reflected positively on technology. Technological developments also enriched the educational activities, and led to the emergence of different teaching styles. Because of that technology plays an intensive part in our lives, it has been admitted in general that it has significant effects on learning and behaviors of human (Senel and Gençoglu, 2003; Martinovic and Zhang, 2012; Celik, et.al, 2009). According to Usta and Korkmaz (2010)’s opinions, teachers and students are also expected to have knowledge and awarenes in the field information and communication technologies as well as having the perception of competence for computer use. Teacher qualifications have very important influence on advancing quality of learning outcomes to upper level. One of the features of qualified teachers is to have competency of using information and communication technologies in a dynamic way in the teaching-learning processes (Seferoglu, 2004; Celik and Kahyaoglu 2007; Usta and Korkmaz, 2010; Akinci, Kurtoglu and Seferoglu, 2012). The use of technology in schools is considerably important (Akkoyunlu, 1995; Turan, 2002;Askar and Olkun, 2005; Ozturk, 2013). Teacher’s use of technology in education in a dynamic way means using information of educational field(FI), pedagogical information (PI) and technological information as being integrated with each other. Using these information as being integrated with each other gained the concept, named Technological Pedagogical Field Information (TPFI) , to the literature. TPFI reveals a structure constituted by addition of technology and field of information from Koehler ve Mishra (2005) to the pedagogical field, gained to the literature by Shulman (1986), and blending these three variables (technological information, pedagogical information and field information) with each other. Regarding main components of TPFI; “Technology” covers the relationships between (computer, internet, video, interactive blackboard, e-book and so on tools), “Pedagogy” covers the relationships between ( how teachers get information, how they configure it, how they ? Assoc. Prof. Dr./Fırat University Education Faculty, Dept. of Educ. Sciences ?? Expert,/Fırat University, Distance Training Center 292 develop positive attitudes towards learning,learning and teaching methods, strategies, processes), and “field-content” information covers the relationships between (basic concepts that teachers learn and teach, and those in their own educational fields) (Kuskaya-Mumcu et.al., 2008; Kula, 2015). There are seven components of TPFI(Mishra and Koehler, 2006). These components and their meanings are as follows; ? Field Information(FI) : Information that educator will learn and teach regarding his branch. ? Pedagogical Information (PI): Teaching approaches, strategies and the knowledge of what approach would be appropriate for the subject to be taught. ? Technological Information (TI): Knowledge of more advanced technologies such as digital video, internet. ? Pedagogical Field Information(PFI):Usage of pedagogical information with field information together. ? Technological Pedagogical Information(TPI): Information about how teaching can be changed by using certain technological devices in the teaching environments. ? Technological Field Information (TFI): Information in which technology and field information are interrelated. ? Technological Pedagogical Field Information(TPFI):Consists of a combination of technology, pedagogy and field information and is the whole of information, different from each part of the whole and far more further of them It seems that there is a tendency toward use of technology for educational purposes. Therefore, change of teacher qualifications is inevitable (Sunbul, 2001; Sonmez, 2003). Indeed, there has been a transformation toward understanding of techno pedagogics, in which pedagogical field information and technology are integrated, and which will keep teacher training and defining of competencies from the effect of behavioral approach (TEA, 2009). Especially recently, it has been seen that technology couldn’t be integrated into the classroom environments despite the large investment made to classroom technology (Kayaduman, Sırakaya and Seferoglu, 2011; Ciftci, Taskaya and Alemdar, 2013). It has been stated in the literature that effective field competencies such as love, values and adaptation towards their profession, as well as cognitive and psychomotor education they receive (McKeachie, 1997) have substantially been effective on teachers’ professional development efforts such as improving the qualifications they have, use of technology in learning environments (Celikoz and Cetin, 2004) Therefore, having positive attitude towards their profession is important for professional development and achievements of teachers. Teachers’ professional attitudes affect students' personality development, teacherstudent relations, teachers' professional successes, and accordingly students’ learning processes (Guclu, 2000; Kucukahmet, 1976; Yasar, Sozer and Gultekin, 2000; Morgan, 1999; Er-dem, Gezer and Cokadar, 2005). That is why a part of educational studies mentioned about teachers’ attitudes and teachers candidates’ attitudes towards teaching profession. Capa and Cil (2000), Dogan and Çoban (2009), Terzi and Tezci (2007), Pehlivan (2008), Kaya and Buyukkasap (2005), Bozdogan, Aydın and Yıldırım (2007), Aslan and Akyol (2006), Hacıomeroglu and Sahin-Taskın (2010) can be given as examples for studies, mentioning about attitudes towards teaching profession. Some studies investigated attitudes of teacher candidates who are not graduate of a faculty of education, towards teaching profession and thus, status of being a student or graduate 293 of faculty of education was intented to reveal in terms of attitude towards profession. It was reported in the studies (Kavcar, 1998; Eraslan and Cakıcı, 2011) performed that students who selected different career field at first have to be investigated from many aspects such as becoming teacher candidate later on, their professional competences, and attitudes towards the profession. Undoubtedly, teachers’ development of positive attitudes towards the profession depends on many variables. TPFI is considered to be one of these variables. Teachers’ abilities and challenges of using of technological elements in classroom will have effect on their professional attitudes to some extent. It was seen when some studies ( Gomleksiz and Fidan, 2011; Dundar and Karaca, 2013; Polat, 2013; Altinkurt, Yılmaz, and Erol, 2014) were examined that despite pedagogical formation program students’ attitudes towards teaching profession were examined in terms of many variables, the relationship between their these attitudes and TPFI competencies weren’t examined. Pedagogical information received during formation education; information towards field information, received during undergraduate education; perception towards technology may be effective on a teacher candidate’s attitude towards teaching profession. On the basis of this basic supposition, perceptions of teacher candidates, studying in pedagogical formation training certificate program, towards technological pedagogical field information, their attitudes towards the teaching profession and the relationships between them were investigated in this study.
Kitap - Kitap İçinde Yayın (Bölüm ya da Makale)
Keywords: Technopedagogical content knowledge; Attitudes; Teaching profession